(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This study evaluated the impact of medical-biological factors on the physical and cognitive development of school-age children (7-12 years). Clinical-neurological and pediatric examinations of N=245 schoolchildren at the Andijan State Medical Institute revealed that perinatal pathologies, genetic predisposition, and chronic diseases impede physical growth and induce cognitive dysfunctions. Anthropometric and psychological (Wechsler scale) data analysis (p < 0.05) confirmed that children with a history of pregnancy toxicosis, hypoxia, and premature birth exhibit ADHD and developmental delays 28.4% more frequently. Early differential diagnostics and personalized health programs are strategically crucial for pediatric practice.